2019
DOI: 10.7150/thno.31893
|View full text |Cite
|
Sign up to set email alerts
|

Gold Clusters Prevent Inflammation-Induced Bone Erosion through Inhibiting the Activation of NF-κB Pathway

Abstract: Inflammation-induced bone erosion is a major pathological factor in several chronic inflammatory diseases that often cause severe outcomes, such as rheumatoid arthritis and periodontitis. Plenty of evidences indicated that the inflammatory bone destruction was attributed to an increase in the number of bone-resorbing osteoclasts. However, anti-resorptive therapy alone failed to prevent bone loss in an inflammatory condition. Conventional anti-inflammation treatments are usually intended to suppress inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…An interesting question for future investigations would be whether the Pro-B cells can transdifferentiate to osteoclasts in the absence of monocytes, and whether this process is affected by inflammatory conditions which are known to stimulate osteoclastogenesis 57 , 58 . In our primary cultures, we could trace the differentiation of B cells to osteoclasts, but we cannot completely rule out the possibility that sporadic monocytes that did not reach the level of detection by flow cytometry were still present.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting question for future investigations would be whether the Pro-B cells can transdifferentiate to osteoclasts in the absence of monocytes, and whether this process is affected by inflammatory conditions which are known to stimulate osteoclastogenesis 57 , 58 . In our primary cultures, we could trace the differentiation of B cells to osteoclasts, but we cannot completely rule out the possibility that sporadic monocytes that did not reach the level of detection by flow cytometry were still present.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the Au cluster may provide an alternative to traditional antirheumatic drugs with more effectiveness and safety. 16,17…”
Section: Introductionmentioning
confidence: 99%
“…[101] A recent study using a CIA model found that a peptide-coated gold cluster exerted antiinflammatory and anti-osteoclastogenesis effects via nuclear factor kappa-B (NF-κB) inhibition. [102] Biomimetic folate-chitosan-DNA NPs also decreased the osteoclast population in the AIA model by regulating osteocalcin, alkaline phosphatase, and tartrate-resistant acid phosphatase. [103] Song et al recently found that vascular EC-secreted exosomes not only presented more effective bone targeting than other cell-derived exosomes, but also inhibited osteoclast formation via its endogenous cargo miR-155.…”
Section: Osteoclastmentioning
confidence: 98%